2011
DOI: 10.1093/hmg/ddr246
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-synuclein functions in the nucleus to protect against hydroxyurea-induced replication stress in yeast

Abstract: Hydroxyurea (HU) inhibits ribonucleotide reductase (RNR), which catalyzes the rate-limiting synthesis of deoxyribonucleotides for DNA replication. HU is used to treat HIV, sickle-cell anemia and some cancers. We found that, compared with vector control cells, low levels of alpha-synuclein (α-syn) protect S. cerevisiae cells from the growth inhibition and reactive oxygen species (ROS) accumulation induced by HU. Analysis of this effect using different α-syn mutants revealed that the α-syn protein functions in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 76 publications
3
45
0
Order By: Relevance
“…ASYN was reported to colocalize with histone 3, in vivo, and to form a tight 2 : 1 complex with purified histones, in vitro, which dramatically accelerated the rate of ASYN fibrillization [246]. Although it has been described that ASYN directly inhibits histone 3 acetylation [259], it was proposed that different expression levels of the protein or the presence of specific cellular stressors may shift effects of ASYN from inhibiting histone acetylation to promoting acetylation [266] (Fig. 4, 1A).…”
Section: Putative Functions Of Asyn In the Nuclear Compartmentmentioning
confidence: 95%
See 2 more Smart Citations
“…ASYN was reported to colocalize with histone 3, in vivo, and to form a tight 2 : 1 complex with purified histones, in vitro, which dramatically accelerated the rate of ASYN fibrillization [246]. Although it has been described that ASYN directly inhibits histone 3 acetylation [259], it was proposed that different expression levels of the protein or the presence of specific cellular stressors may shift effects of ASYN from inhibiting histone acetylation to promoting acetylation [266] (Fig. 4, 1A).…”
Section: Putative Functions Of Asyn In the Nuclear Compartmentmentioning
confidence: 95%
“…It was initially proposed that the C-terminal region of the protein is required for its nuclear translocation [248,264] but two recent studies have demonstrated that this event is driven by the N-domain of the protein [265,266]. Regardless of which mechanisms are involved in ASYN nuclear translocation, several factors have been proposed to play a role in this process.…”
Section: Nuclear Translocation Of Asynmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were periodically removed to determine the number of viable cells in culture. Previous studies have shown that α-syn significantly shortens the CLS of yeast [17] and induces ROS to accumulate [18]. …”
Section: Resultsmentioning
confidence: 99%
“…Maybe α-syn inhibits oxidative stress during heme and hemoglobin synthesis in RBC progenitor cells and this function is also required in RBCs. Perhaps not surprising, antioxidant functions of α-syn have been reported [30,3743]. …”
Section: The Structure and Function Of α-Synmentioning
confidence: 97%